Health-Related Problems among Retirees in Enugu East Senatorial Zone of Enugu State - Ugwu, Cosmas Uchenna; Ugwu, Cosmas Uchenna (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The purpose of the study was to ascertain health-related problems –HRPs among retirees in Enugu East Senatorial Zone of Enugu State. Three research questions and two null hypotheses guided the study. The study adopted descriptive survey research design. The population for the study consisted of all the registered retirees in Enugu East Senatorial Zone of Enugu State totaling 2173 pensioners. A total of 324 respondents were randomly sampled. A researcher designed questionnaire known as HRPQ was used for data collection. Face validity of the instrument was established through constructive criticism of three experts. The reliability index of .77 was obtained. The statistical tools used for data analysis include mean, standard deviation, t-Test and ANOVA. The study revealed that weight problems, back pains, painful joints (Arthritis), loss of balance, loss of strength, cramps, bone problems, joint problems, cardiac or heart problems, hearing problems, vision and eyesight problems, foot problems, knee Osteoarthritis, loss of memory, and loss of attention constitute their ageing problems. It was also found that HRP differ according to gender and marital status. Based on the findings, recommendation was made that health workers, government and non-governmental organizations should embark on collaborative efforts in organizing conferences and seminars, focusing on educating the general public and employees in particular on the nature of health-related problems and appropriate measures for ameliorating them.